Incorporating knowledge of changes in climatic, oceanographic and ecological conditions in Canadian stock assessments - Pierre Pepin; Jacquelyne King; Carrie Holt; Helen Gurney‐Smith; Nancy Shackell; Kevin Hedges; Alida Bundy (Fish and Fisheries, 2022)
Environmental impacts on fisheries are pervasive, yet methods to account for them in stock assessments and management decisions vary in rigour and quality. The prevalence and efficacy of methods to account for environmental impacts are not well documented, limiting our ability to adequately respond to future environmental and climate changes for adaptive resource management. In Canada, legislation now requires that environmental conditions are considered in the management of fish stocks, yet the current extent of implementation in assessment processes is poorly understood. We assessed the use of climate, oceanographic and ecological considerations in science advisory processes for 178 stock assessments by Fisheries and Oceans Canada. We evaluated whether these considerations were included in conceptual hypotheses about broad‐scale mechanisms, quantitative or qualitative analyses, and the development of management advice on current or future stock status. Conceptual hypotheses were included in 46% of assessments; quantitative inclusions occurred in 21% of assessments, while qualitative interpretations appeared in 31% of assessments; and 27% of assessments included climate, oceanographic and/or ecological considerations in the advice. Assessments of salmonids, invertebrates and pelagic taxa more frequently made use of environmental data than those for groundfish and elasmobranchs. Comparing our findings with assessments in other jurisdictions highlighted a gap in Canada's ability to respond to environmental changes and a need to develop integrated management approaches, such as regional ecosystem assessments and approaches that combine modelling and empirical analyses, with socio‐economic analysis within interdisciplinary teams.

Exploring ecosystem‐based management in the North Atlantic - Mark Dickey‐Collas; Jason S. Link; Paul Snelgrove; J. Murray Roberts; M. Robin Anderson; Ellen Kenchington; Alida Bundy; Margaret M. (Peg) Brady; Rebecca L. Shuford; Howard Townsend; Anna Rindorf; Murray A. Rudd; et al. (Journal of Fish Biology, 2022)
The United States, the EU and Canada established a trilateral working group on the ecosystem approach to ocean health and stressors under the Atlantic Ocean Research Alliance. Recognizing the Atlantic Ocean as a shared resource and responsibility, the working group sought to advance understanding of the Atlantic Ocean and its dynamic systems to improve ocean health, enhance ocean stewardship and promote the sustainable use and management of its resources. This included consideration of multiple ocean‐use sectors such as fishing, shipping, tourism and offshore energy. The working group met for 4 years and worked through eight steps that covered the development of common language as a basis for collaboration, challenges of stakeholder engagement, review of the governance mandates, exploring the links between sectors and ecosystems effects, identifying gaps in knowledge and uptake of science, identification of tools for ecosystem‐based management, customary best practice for tool development and communication of key research priorities. The key findings were that ecosystem‐based management enables new benefits and opportunities, and that we need to make the business case. Further findings were that adequate mandates and effective tools exist for ecosystem‐based management, and that ecosystem‐based management urgently requires integration of human dimensions, so we must diversify the conversation. In addition, it was found that stakeholders do not see their stake in ecosystem‐based management, so greater engagement with stakeholders and targeting of ocean literacy is required and a sustainable future requires a sustained investment in ecosystem‐based management, so long‐term commitment is key.